Characterization and control of Shape Memory Alloy-based actuators for heavy payloads displacement - Dorin Copaci; Andres Lopez Palenzuela; Luis Moreno; Santiago Martínez; Carlos Balaguer (Results in Engineering)
Today, it is of vital importance to research actuators and its control to harness their advantages, such as the force-to-weight ratio of the actuator or its energy consumption, in a more efficient way. For this reason, this work describes the characterization and control of actuators based on Shape Memory Alloy wires with different diameters ranging from 0.5 to 2 mm. These Nickel Titanium wires contract in length when heated, which makes them a distinguishing property compared to other alloys. This contraction is used to apply force so that it can be used in applications such as moving objects, controlling valves, or designing exoskeletons, among others. In this context, the objective of this work is to characterize Shape Memory Alloy wires of varying diameters, ranging from 0.5 mm to 2 mm, which are capable of lifting loads exceeding 100 kg with a single wire, while maintaining controlled positioning. Among the parameters to be highlighted are cooling and heating times, speed, energy consumption, breaking limits, and duty cycles. Additionally, various heating methods for Shape Memory Alloys wires are analyzed: direct heating by Joule effect and external heating. The results obtained with the proposed control strategy for steady-state position control (when the output remains within ±5% of the final value) were as follows: RMSE of 0.0401% for the one-way 0.51 mm wire, 0.0483% for the two-way 0.51 mm wire, 0.289% for the 1 mm wire, and 0.0857% for the 2 mm wire.